PENGARUH PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING (GUIDED INQUIRY) BERBANTUAN LEMBAR KERJA SISWA TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA PADA MATERI KOLOID - Fiza Sulastri; Lisa utami; Zona Octarya (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2019)
AbstractThis research was instigated by the low of students creative thinking ability at State Senior High School 1 Perhentian Raja. This research aimed at knowing the effect of implementing Guided Inquiry learning model with student workbook toward student creative thinking ability on Colloid lesson at State Senior High School 1 Perhentian Raja.  It was Quasi Experimental research.  Simple Random Sampling technique was used in this research.  The samples comprised two classes, the eleventh-grade students of Natural Science 1 that were 33 students as the Control group and the students of Natural Science 2 that were 32 studentsas the Experimental group. The techniques of collecting the data were tests in the form of homogeneity test as the preliminary data, pretest and posttest as the final data, observation, and documentation. The instrument of this research was creative thinking ability test in the form of essay with the indicators of fluency, flexibility, originality, and elaboration. The pretest and posttest data were analyzed by using t test at 5% significant level.  The research findings showed that there was a significant effect of implementing Guided Inquiry learning model with student workbook toward student creative thinking ability on Colloid lesson that t was 4.268 and the score of Sig. (2-tailed) was 0.00.  The coefficient of effect was 22%. Keywords: Guided Inquiry Learning Model, Student Workbook Guided Inquiry Based, Creative Thinking Ability, Colloid